ADAPTIVE HUMAN RESOURCE DEVELOPMENT IN SUPPORTING SUSTAINABLE DEVELOPMENT BASED ON GEO-TOURISM IN THE LAKE TOBA CALDERA AREA - Kholilul Kholik; Siti Hajar (Iapa Proceedings Conference, 2025)
This study aims to analyze how the Adaptive Human Resource Development (AHRD) approach can be a strategic framework in developing local human resource capacity to support sustainable development based on geotourism in the Toba Caldera Area in Samosir Regency, and uses a qualitative approach. The results of the study indicate that the implementation of AHRD integrated with local wisdom values, mastery of digital technology, and strengthening community institutions can be an important foundation in improving the quality of local human resources that are responsive to change and able to play an active role in environmental conservation, sustainable tourism management, and improving community welfare.